Rapid variability of the arcsec-scale X-ray jets of SS 433 - Migliari, S; Fender, R; Blundell, K; Mendez, M; Klis, M (2005)
We present the X-ray images of all the available Chandra observations of the galactic jet source SS 433. We have studied the morphology of the X-ray images and inspected the evolution of the arcsec X-ray jets, recently found to be manifestations of in situ reheating of the relativistic gas downstream in the jets. The Chandra images reveal that the arcsec X-ray jets are not steady long term structures; the structure varies, indicating that the reheating processes have no preference for a particular precession phase or distance from the binary core. Three observations made within about five days in May 2001, and a 60 ks observation made in July 2003 show that the variability of the jets can be very rapid, from timescales of days to (possibly) hours. The three May 2001 images show two resolved knots in the east jet getting brighter one after the other, suggesting that a common phenomenon might be at the origin of the sequential reheatings of the knots. We discuss possible scenarios and propose a model to interpret these brightenings in terms of a propagating shock wave, revealing a second, faster outflow in the jet.